2017
DOI: 10.5114/cipp.2017.67230
|View full text |Cite
|
Sign up to set email alerts
|

Entitlement attitude in the workplace and its relationship to job satisfaction and organizational commitment

Abstract: background This article is focused on the entitlement attitude in an organizational context. Its purpose was to examine the relationship of entitlement and its 3 components (active, passive and revengefulness) with job satisfaction and organizational commitment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…When entitled consumers have unmet expectations, they often experience a sense of injustice or betrayal that sparks a desire for revenge against the service provider [ 61 ]. This revengefulness is based in an entitled belief that individuals have the right to harm others who have insulted them [ 62 ]; for consumers, revenge often comes in the form of negative word of mouth [ 63 , 64 ]. Similarly, academically entitled students are more likely to report a desire to seek revenge and undermine their professors' credibility in response to perceived injustice, for example, an undesirable grade or class policy [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…When entitled consumers have unmet expectations, they often experience a sense of injustice or betrayal that sparks a desire for revenge against the service provider [ 61 ]. This revengefulness is based in an entitled belief that individuals have the right to harm others who have insulted them [ 62 ]; for consumers, revenge often comes in the form of negative word of mouth [ 63 , 64 ]. Similarly, academically entitled students are more likely to report a desire to seek revenge and undermine their professors' credibility in response to perceived injustice, for example, an undesirable grade or class policy [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…These authors have suggested that highly entitled employees report higher job frustration which, in turn, is associated with insulting co-workers, behaving rudely, and undermining co-workers' positions with supervisors while simultaneously promoting themselves [15,17,25]. Studies have also shown that employees who feel highly entitled are also more likely to experience lower job satisfaction [20,7,8,2] and higher levels of burnout and stress [10]. Several explanations for these findings have been offered.…”
Section: Psychological Sense Of Entitlement In the Workplacementioning
confidence: 99%
“…Previous studies have revealed that employees' sense of entitlement has significant implications for their functioning in the workplace, and thereby for overall organizational performance and outcomes. For example, it was found that entitled employees reported having more conflicts with their supervisors, lower job satisfaction [9,10], thoughts regarding quitting their jobs [11], abusiveness toward coworkers [11], unethical pro-organizational behavior [12], and increased levels of aggressive behaviors [13][14][15] suggested that feelings of being entitled are a result of these individuals' inclination toward feeling that they are being mistreated by others. Although most studies have revealed associations between employees' sense of entitlement and negative outcomes [16][17][18], a number of studies have indicated that employees' sense of entitlement might also be associated with positive outcomes [19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Research also found entitlement to be related to conflicts with supervisors (Harvey & Martinko, 2009), conflicts with coworkers (Harvey & Harris, 2010), negative reactions to criticism, and high levels of selfishness (Campbell et al, 2004). Employees who feel entitled also tend to display low levels of job satisfaction and organizational commitment (Asenova & Koleva, 2018).…”
Section: Entitlement and Technology Addictionmentioning
confidence: 99%